L’Orazio di Nisbet – Rudd. Riflessioni sull’arte del commentare - Fedeli, Paolo (Exemplaria Classica, 2009)
<p class="MsoNormal" style="text-align: justify; margin: 0cm 0cm 0pt; mso-pagination: widow-orphan; mso-hyphenate: auto; tab-stops: 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt;"><span style="font-family: ";ALPHABETUM Unicode";; color: windowtext; mso-bidi-font-family: ’Courier New’; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ES; mso-bidi-language: AR-SA;" lang="EN-US">Nisbet-Rudd Commentary on III Horace’s book of Carmina is the starting point for a reflection upon the contemporary commentaries and upon the commentary technique.